Clinical Characteristics and Outcomes in Patients with Ruptured Middle Cerebral Artery Aneurysms: A Multicenter Study in Northern China - Xiuhu An; Jingliang Su; Bingxin Duan; Long Zhao; Bangyue Wang; Yan Zhao; Tianxing Li; Shuai Zhou; Xinyu Yang; Zhenbo Liu (Neurology and Therapy)
Abstract Introduction The long-term prognosis of ruptured middle cerebral artery aneurysms (MCAAs) in northern China remains unclear. The aim of this study is to analyze the epidemiological characteristics and long-term outcomes of ruptured MCAAs in northern China. Methods We included patients who were consecutively admitted for ruptured MCAAs to 12 tertiary care centers in northern China from January 2017 to December 2020. Kaplan‒Meier curves were used to compare survival in hazard strata. The Cox proportional hazards model was used to analyze risk factors and mortality risk, whereas logistic regression was used to identify factors influencing 2-year survival. Subgroup analyses were performed to verify the robustness of the results. Results Data on 959 patients with ruptured MCAAs were analyzed; 16.4% of these patients had ruptured intracranial aneurysms (RIAs) and were registered in the Chinese cerebral aneurysm database. The mean follow-up duration was 3.0 years (range 0–6.2 years). The 3-month and 2-year mortality rates were 15.5% and 18.2%, respectively. The risk factors for mortality were identified via Cox regression and were as follows: age > 70 years, previous stroke, combined intracerebral hemorrhage (ICH)/intraventricular hemorrhage (IVH), poor Hunt and Hess grade, multiple aneurysms, and conservative treatment (CT). The positive association between the risk of death and CT was consistent across subgroups. According to logistic regression, hypertension, previous stroke, combined ICH/IVH, Hunt and Hess grade, and WFNS (World Federation of Neurological Surgeons) score were identified as factors negatively influencing 2-year survival. Conclusion We detail the epidemiologic characteristics and long-term outcomes of MCAAs. The risk factors for mortality included age > 70 years, previous stroke, combined ICH/IVH, poor Hunt and Hess grade, and multiple aneurysms. Compared with microsurgical treatment (MST), CT is associated with an increased risk of mortality, while the risk of mortality associated with endovascular treatment (EVT) is not significantly different. Two-year survival was associated with hypertension, previous stroke, ICH/IVH, and poor grades at admission.